Разложить на множители: 2х (во второй степени)-5х - 3

dadfxhg dadfxhg    1   03.09.2019 14:20    0

Ответы
IlonaLike IlonaLike  06.10.2020 14:56
2x² - 5x - 3 = 2( x + 0,5 )( x - 3 ) = ( 2x + 1 )( x - 3 )

D = ( - 5 )² - 4 * 2 * ( - 3 ) = 25 + 24 = 49 = 7²
x1 = ( 5 + 7 ) : ( 2 * 2 ) = 12 : 4 = 3 
x2 = ( 5 - 7 ) : ( 2 * 2 ) = - 2 : 4 = - 0,5
ПОКАЗАТЬ ОТВЕТЫ
yuldumenko yuldumenko  06.10.2020 14:56
2x²-5x-3=2(x+1/2)(x-3)=(2x+1)(x-3)
D=25+24=49
x1=(5-7)/4=-1/2
x2=(5+7)/4=3
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика